Theoretical Foundations of Machine Learning as a Pillar for Smart Computational Systems - Rizky A, Galih Prakoso (IHSA Institute, 2025)
This research explores the theoretical foundations of Machine Learning (ML) as a critical pillar for the development of smart computational systems. The study emphasizes the importance of core ML paradigms supervised, unsupervised, and reinforcement learning in providing the basis for intelligence, adaptability, and efficiency in modern computational models. By synthesizing theoretical insights with recent advancements, this research demonstrates how a deeper understanding of ML principles improves model design, reduces errors, and enhances the reliability of intelligent systems. The findings highlight that while ML theories significantly contribute to performance and innovation, challenges such as data bias, overfitting, interpretability, and computational limitations remain pressing concerns. Addressing these issues requires not only methodological improvements but also ethical and interdisciplinary approaches. In conclusion, this research affirms that ML theory is not merely academic but serves as a practical backbone for applied innovation, ensuring the development of systems that are robust, transparent, and sustainable. Future directions should focus on bridging theoretical advancements with real-world applications to strengthen the role of ML as a foundation for next-generation computational intelligence.